Analysis of the clinical manifestations and diagnostic process of the pleural effusion associated with constrictive pericarditis - Wei, Weifeng; Shen, Panxiao; Liu, Shaowei; Li, Naijian; Zeng, Yunxiang; Ma, Lunchao; Wang, Jinlin (Frontiers in Medicine, 2024)
Objectives The primary objective of this study is to analyze the clinical manifestations, diagnostic procedures, and outcomes of patients with pathologically confirmed constrictive pericarditis who presented with bilateral pleural effusions. We aim to outline a stepwise diagnostic approach that could assist clinicians in identifying CP in similar cases. Methods In this study, we conducted a retrospective analysis of 19 cases of pathologically confirmed constrictive pericarditis. These patients were admitted to our hospital between January 2019 and December 2022 after pericardial stripping. The collected data included imaging findings, clinical manifestations, pleural effusion characteristics, postoperative pathology, and the diagnostic process. Results In this study, the age of the 19 patients ranged from 25 to 74 years, with a median age of 59 years. All patients presented with bilateral pleural effusions, with or without pericardial lesions such as pericardial effusion or thickening. Pleural effusion biochemistry did not exhibit specific characteristics, and both etiology and pleural pathology were negative. Radiographic examinations, including cardiac ultrasound and chest CT, revealed signs of pericardial thickening and/or pericardial effusion or no abnormalities. Pericardial stripping was performed in all patients, and the postoperative pathology confirmed various degrees of thickened pericarditis, consistent with constrictive pericarditis. During a follow-up period of 6–18 months, most patients (17 out of 19) showed favorable recovery with no recurrence of bilateral pleural effusions. Conclusion This study emphasizes the importance of pleural effusion as a clinical sign of constrictive pericarditis and highlights that a stepwise diagnostic approach, guided by clinical presentation and imaging, can enhance its recognition, particularly in cases with bilateral pleural effusions.